2020
DOI: 10.3390/nano10122491
|View full text |Cite
|
Sign up to set email alerts
|

Copper Surfaces in Biofilm Control

Abstract: Biofilms are structures comprising microorganisms associated to surfaces and enclosed by an extracellular polymeric matrix produced by the colonizer cells. These structures protect microorganisms from adverse environmental conditions. Biofilms are typically associated with several negative impacts for health and industries and no effective strategy for their complete control/eradication has been identified so far. The antimicrobial properties of copper are well recognized among the scientific community, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 138 publications
0
14
0
1
Order By: Relevance
“…In fact, biofilms play an important role in the development of bacterial resistance against antibiotics and other antibacterial agents [63]. Numerous studies have shown that metal-based NPs, including AuNPs [64], AgNPs [65], MgONPs [66], ZnONPs [67], and CuONPs [68], can prevent or overcome biofilm formation.…”
Section: Metal-based Nanoparticles Target Ros Production In Bacteriamentioning
confidence: 99%
“…In fact, biofilms play an important role in the development of bacterial resistance against antibiotics and other antibacterial agents [63]. Numerous studies have shown that metal-based NPs, including AuNPs [64], AgNPs [65], MgONPs [66], ZnONPs [67], and CuONPs [68], can prevent or overcome biofilm formation.…”
Section: Metal-based Nanoparticles Target Ros Production In Bacteriamentioning
confidence: 99%
“…Copper, along with silver, belongs to the most widespread class of antimicrobial surfaces, in the case of which the antibacterial active agent is constantly released from the coatings [13]. One of the drawbacks of such surfaces is the accumulation of dead bacterial mass on the surfaces and, thus, the blocking of the active and metal-ion-releasing surface [14]. This issue could be resolved by the use of reactive in-situacting photocatalytic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by the SEM images in Figure , the treatment of P. syringae (as an example) with the SLC Cu-BTC MOFs led to abnormal blebbing of the bacterial cell membrane, indicating weakening of the cell membrane. This further suggests that the interaction of the bacterial cells with the Cu 2+ ions on the surface of the SLC Cu-BTC MOFs resulted in cell membrane destabilization, therefore making them more vulnerable to subsequent lysis by physical forces. Such an assertion is also consistent with the observation of the normal morphology of bacterial cells that were treated with the cubic Cu-BTC MOFs.…”
Section: Discussionmentioning
confidence: 94%